Mitoautophagy: A Unique Self-Destructive Path Mitochondria of Upper Motor Neurons With TDP-43 Pathology Take, Very Early in ALS - Gautam, Mukesh; Xie, Edward F.; Kocak, Nuran; Ozdinler, P. Hande (Frontiers in Cellular Neuroscience, 2019)
Mitochondrial dysfunction is one of the converging paths for many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), and TDP-43 pathology is the most common proteinopathy detected in ALS and ALS/Frontotemporal lobar degeneration (ALS/FTLD). We recently identified mitochondrial problems in corticospinal motor neurons (CSMN) and in Betz cells of patients with TDP-43 pathology. However, the timing and the extent of mitochondrial defects, and their mode of degeneration have not been revealed. Because it is important to reveal when problems first begin to emerge and whether they are shared or unique, we investigated the health and integrity of mitochondria in CSMN of prpTDP-43A315T, PFN1G118V, and hSOD1G93A mice at P15 (post-natal day 15)—a very early age in mice without any sign of cellular degeneration.Utilization of immuno-coupled electron microscopy for a detailed surveillance of mitochondria in CSMN and other non-CSMN cells revealed presence of a novel self-destructive path of mitochondrial degeneration, which we named mitoautophagy. Mitoauthopgy is different from mitophagy, as it does not require autophagosome-mediated degradation. In contrast, in this novel path, mitochondria can clear themselves independently. We find that even at this early age, all diseased CSMN begin to display mitochondrial defects, whereas mitochondria in non-CSMN cells are healthy. Our findings not only reveal mitoautophagy as a novel path of mitochondrial clearance that occurs prior to neuronal vulnerability, but it also highlights that it is present mainly in the upper motor neurons of prpTDP-43A315T and PFN1G118V mice, which mimic many aspects of the disease in patients with TDP-43 pathology.